Determinants Fraudulent Financial Statements Using the S.C.O.R.E Model on Infrastructure Sector Companies in Indonesia - Edy Anan (Ilomata International Journal of Tax and Accounting, 2021)
The infrastructure sector is the top priority of the Indonesian government's development from 2014 to 2019. Indonesia Corruption Watch (ICW) data shows that the number of corruption cases in infrastructure projects has increased during 2015-2018. The value of losses in corruption cases in infrastructure projects is estimated at 1.1 trillion rupiah. The results of various studies on the factors affecting fraudulent financial statements show inconsistent results. This research aims to determine the impact of the stimulus, ability, opportunity, rationalization, and self on companies' fraudulent financial statements in the infrastructure industry listed on the Indonesian Stock Exchange (IDX). This study uses quantitative research methods. Sampling techniques use purposeful sampling, that is, hypothesis testing using logistic regression analysis models. The results showed that the stimulus measures had a positive and significant impact on fraudulent financial statements. Competence, opportunity, and rationalization have a positive and insignificant impact on fraudulent financial statements. The impact of self on fraudulent financial statements is negligible. The research supports the agency theory that management can commit fraudulent financial statements and achieve the Company's financial goals.